Exemples d'antonomasie dans l'Oraison funèbre de S. Basile de Césarée (BHG 245) Un nom peut en cacher un autre - Demoen, Kristoffel (Analecta Bollandiana, 1994)
The rhetorical device of the (Vossian) antonomasia, which substitutes the name of a (biblical) character for a contemporary person, can reveal, in Christian authors, a typological point of view.